ANALISIS PELAKSANAAN SISTEM PENGELUARAN KAS PADA DINAS KESEHATAN PROVINSI NUSA TENGGARA TIMUR - Abrius Morison Pibo; Deetje W. Manuaian; Munawar Munawar (P3M- Politeknik Negeri Kupang, 2021)
As a public sector organization engaged in public health, the NTT Provincial Health Office implements a financial recording and management mechanism thet also discuses cash disbursement. Problems that occur in financial recording and management, implementation often experience delays in a functional letter of accountability (SPJ) due to delays in documents or detailed expenditures given by the Activity Technical Implementation Officer to the expenditure treasurer. Meanwhile, the expenditure treasurer must prepare a cash closing report, recapitulate the amounts of spending and other related items, and combine the results of the recapitulation with the results in the assistant expenditure treasurer. Data collection tecniques using interviews, observation and document study. The data analysis used descriptive qualitative method with the stages of data reduction, data presentation, and conclusion drawing. The results howed that the functions/parties involved in the implementation of the cash disbursement system were the same and appropriate, while the documents and records used were in accordance with Permendagri No.21 of 2011, except: 1. Order for Payment of Supply Money (SPP-UP), 2. Order for Additional Money Supply (SPP-TU). It is recommended that: 1. It is recommended that the East Nusa Tenggara Provincial Health Officw is in contact with the Supply Money Payment Order, the Supply Money Payment Order (SPP-GU), the Add Inventory Payment Order (TU) in the implementation of the cash disbursement system needs to be adjusted